Effects of a Remote Antimicrobial Stewardship Program on Antimicrobial Use in a Regional Hospital System - Joshua Knight; Jessica Michal; Stephanie Milliken; Jenna Swindler (MDPI AG, 2020)
While antimicrobial stewardship programs (ASPs) are well established at most large medical centers, small or rural facilities often do not have the same resources; therefore, different methods must be developed to start or expand ASPs for these hospitals. The purpose of this quality improvement study was to describe the implementation of a pharmacist-led remote ASP and assess the effect on antimicrobial use. Antimicrobial use in days of therapy per 1000 patient days (DOT/1000 PD) was compared between the six months before and after remote ASP implementation. Changes in system-wide, facility-specific, and target antimicrobial use were evaluated. Pharmacist interventions, acceptance rates, and number of times infectious disease (ID) physician assistance was sought were also tracked. System-wide antimicrobial use was 4.6% less in the post-implementation time period than in the pre-implementation time period, with vancomycin, piperacillin/tazobactam, and fluoroquinolones having the greatest reductions in use. Ninety-one percent of interventions made during the post-implementation period were accepted. ID physician review was requested 38 times, and direct ID physician intervention was required six times. Remote ASPs delivered from a central facility to serve a larger system may reduce antimicrobial use, especially against targeted agents, with minimal increase in ID physician workload.